Ultrastructure of the proboscis in Cystiplanidae, (Plathelminthes, Kalyptorhynchia) - De Vocht, A. (Zoomorphology, 1989)
The fine structure of the proboscis epithelia and musculature of the kalyptorhynchs Cystiplex axi and Cystiplana paradoxa is described. The epithelia are divided into one cellular and four syncytial belts. The former lines the distal part of the cavity and in both species contains a circular groove which has ciliary receptors with modified axonemata. Apart from this cellular belt, two syncytial belts and a part of the belt covering the basal part of the cone form the sheath epithelium. The first two belts of the sheath epithelium, characterised by infoldings of the basal plasma membrane, have intra-epithelial nuclei. The proximal belt lining the cavity is characterised by numerous piercing gland necks. The cone is covered by two syncytia and the basal cone epithelium has microvilli with dense tips. A cytoplasmic girdle at the junction contains the nucleiferous cell parts of the proximal belt of the sheath epithelium and the apical cone epithelium. The insunk nucleiferous parts of the basal cone epithelium are arranged in six groups and are situated proximal to this girdle. Both species possess intra-epithelial muscles in the cone and in the cytoplasmic girdle. The inner and outer musculature are fully described. The results are discussed in the light of previous ultrastructural investigations on Polycystis naegelii and Cicerina remanei and light microscopic information obtained from other species of Cystiplanidae.